2000
DOI: 10.1159/000007046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intracoronary Tissue-Type Plasminogen Activator Treatment in Kawasaki Disease and Acute Myocardial Infarction

Abstract: We retrospectively studied 3 patients with Kawasaki disease (KD) and acute myocardial infarction (AMI) who were treated with intracoronary administration of tissue-type plasminogen activator (t-PA). Two-dimensional echocardiogram on the next day of the treatment revealed reduction of thrombus and improvement of the cardiac function in all 3 patients. However, a 12-month-old patient treated with 200,000 U/kg of t-PA at 48 h after the onset of AMI died of recurrent myocardial infarction. The other 2 patients tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Interventional coronary thrombolysis has been established for adult patients. However, coronary artery openings in children are much narrower, and specialists prefer not to perform similar coronary thrombolysis procedures in infant patients [23][24][25]. In the United States, it has been reported that in the treatment of adult KD coronary thrombosis, thrombolysis should be performed in the coronary artery rst, and if the thrombolysis is not successful, intravenous thrombolysis should be continued (the time is far longer than 12 hours, and the drug has been given for several times), which also achieves good results [17].…”
Section: Discussionmentioning
confidence: 99%
“…Interventional coronary thrombolysis has been established for adult patients. However, coronary artery openings in children are much narrower, and specialists prefer not to perform similar coronary thrombolysis procedures in infant patients [23][24][25]. In the United States, it has been reported that in the treatment of adult KD coronary thrombosis, thrombolysis should be performed in the coronary artery rst, and if the thrombolysis is not successful, intravenous thrombolysis should be continued (the time is far longer than 12 hours, and the drug has been given for several times), which also achieves good results [17].…”
Section: Discussionmentioning
confidence: 99%
“…Case reports of intracoronary and intravenous tPA use in children with KD have been reported with varying success. [8][9][10] We used both intracoronary and intravenous tPA in our patient with the addition of abciximab, a glycoprotein IIb/IIIa inhibitor. Abciximab has been used effectively in adults with acute coronary syndrome but the dosing and duration of therapy with this agent largely remains unknown in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are different applications in different centres. Nakagawa et al applied intracoronary tPA at the dose of 200,000 unit/kg (0.34 mg/kg) to a patient with Kawasaki disease who suffered MI, but the patient died [79]. Subsequently, doses of 400,000 unit/kg (0.69 mg/ kg) and 800,000 unit/kg (1.38 mg/kg) intra-coronary tPA were applied to 2 other patients with Kawasaki disease who suffered MI, and the thrombi and cliinical findings of the patients were determined to have recovered without any complications.…”
Section: Alteplasementioning
confidence: 99%